Pengaruh Rasio Profitabilitas dan Solvabilitas Terhadap Return Saham Perusahaan Sub-Sektor Batu Bara - Sherlina Ayu Dwi Miliyani; Diah Yudhawati; Titing Suharti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine the effect of profitability and laverage ratios on Stock Return both partially and simultaneously in coal sub-sector companies listed on the IDX for the 2017-2021 period. The profitability ratio used is Return On Asset (ROA) and Return on Equity (ROE) while the laverage ratio used is Debt to Equity Ratio (DER) as the dependent variable; The independent variable used is stock return. The sampling method uses the Purposive Sampling method with the number of samples consisting of 9 coal sub-sector companies that meet the criteria. The data analysis methods used are panel data regression analysis, classical assumption test, multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis test using t test and f test. The results showed that partially the ROA variable had a significant negative effect on stock returns, ROE variables had a significant positive effect on stock returns, while the DER variable did not have a significant effect on stock returns. Simultaneously, the variables ROA, ROE, and DER have a significant effect on Stock Return